INVISIBLE RENDEZVOUS: MAPPING THE MUSIC AND COMMUNITY OF COMPUTER MEDIATED COMMUNICATION THROUGH PERFORMANCE (POINT AND COUNTERPOINT). - Plotz, Trudy; Bell, Elizabeth (Text & Performance Quarterly)
Explores the challenges of adapting, directing and performing 'Invisible Rendezvous.' Information on mapping the music of cyberspace through performance; Significance of computer-mediated communication.